2014
DOI: 10.1186/2052-1847-6-4
|View full text |Cite
|
Sign up to set email alerts
|

Regionally accentuated reversible brain grey matter reduction in ultra marathon runners detected by voxel-based morphometry

Abstract: BackgroundDuring the 4,487 km ultra marathon TransEurope-FootRace 2009 (TEFR09), runners showed catabolism with considerable reduction of body weight as well as reversible brain volume reduction. We hypothesized that ultra marathon athletes might have developed changes to grey matter (GM) brain morphology due to the burden of extreme physical training. Using voxel-based morphometry (VBM) we undertook a cross sectional study and two longitudinal studies.MethodsPrior to the start of the race 13 runners volunteer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
14
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(15 citation statements)
references
References 46 publications
0
14
0
1
Order By: Relevance
“…However, neither striatal ROI analysis nor whole brain analysis showed significant correlations. Previous studies showed that the effects of structural brain changes caused by experience-dependent mechanisms are reversible [e.g., sports (Freund et al, 2014), chronic pain (Gwilym et al, 2010), or obsessive-compulsive disorder (Lazaro et al, 2009)]. Dissolution of a romantic relationship has effects opposite to those of forming the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…However, neither striatal ROI analysis nor whole brain analysis showed significant correlations. Previous studies showed that the effects of structural brain changes caused by experience-dependent mechanisms are reversible [e.g., sports (Freund et al, 2014), chronic pain (Gwilym et al, 2010), or obsessive-compulsive disorder (Lazaro et al, 2009)]. Dissolution of a romantic relationship has effects opposite to those of forming the relationship.…”
Section: Discussionmentioning
confidence: 99%
“…Spatial normalization parameters obtained from the segmented mean image were finally applied to the segmentation of the bias-corrected baseline and follow-up images, which were realigned again. Data were not modulated (i.e., scaled by the amount of contraction or expansion during normalization), because scaling is not necessary for longitudinal studies in which the focus is on relative differences between two images of the same participant [46]. In the last step, GM segments (wp1mr*) representing GM volume or density, respectively, were smoothed with a 10 mm full-width-at-half-maximum (FWHM; [47]) Gaussian kernel suitable for small sample sizes [9,48].…”
Section: Mri Data Acquisition and Voxel-based Morphometrymentioning
confidence: 99%
“…Some newer studies also found regionally increased volumes, as did the study by Marsh et al These variable results may reflect the heterogeneity of approaches. Especially important for ED research are the acute effects of starvation, dehydration, and excessive exercise (7,8). Those factors could confound the search for brain alterations that drive or are mechanistically involved in ED behavior by masking them with the consequences of malnutrition.…”
mentioning
confidence: 99%